2016
DOI: 10.1681/asn.2015101169
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Trans–Signaling Links Inflammation with Angiogenesis in the Peritoneal Membrane

Abstract: Vascular endothelial growth factor (VEGF) is implicated in the peritoneal membrane remodeling that limits ultrafiltration in patients on peritoneal dialysis (PD). Although the exact mechanism of VEGF induction in PD is unclear, VEGF concentrations in drained dialysate correlate with IL-6 levels, suggesting a link between these cytokines. Human peritoneal mesothelial cells (HPMCs), the main source of IL-6 and VEGF in the peritoneum, do not bear the cognate IL-6 receptor and are thus unable to respond to classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 63 publications
3
83
0
Order By: Relevance
“…In keeping with previous research showing a robust association between intraperitoneal IL-6 production and faster PSTR (12,21,22), baseline dialysate IL-6 levels were associated with faster PSTR for the duration of follow-up, whereas plasma IL-6 had no effect. Although IL-6 has many immunomodulatory effects (23,24), recent observations linking IL-6 signaling to peritoneal VEGF production provide a mechanism by which IL-6, not itself vasoactive, might alter angiogenesis and vascular permeability in the peritoneal membrane (25).…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with previous research showing a robust association between intraperitoneal IL-6 production and faster PSTR (12,21,22), baseline dialysate IL-6 levels were associated with faster PSTR for the duration of follow-up, whereas plasma IL-6 had no effect. Although IL-6 has many immunomodulatory effects (23,24), recent observations linking IL-6 signaling to peritoneal VEGF production provide a mechanism by which IL-6, not itself vasoactive, might alter angiogenesis and vascular permeability in the peritoneal membrane (25).…”
Section: Discussionmentioning
confidence: 99%
“…9 Importantly, experimental evidence in animal models links persistent peritoneal IL-6 generation to membrane change/fibrosis 10 and angiogenesis. 11 These processes may well bear clinical relevance as is suggested by the results of the Global Fluid Study, a multinational, multicenter, prospective, cohort study in 959 PD patients with up to 8 years of follow-up. Here it was found that local peritoneal and systemic inflammation are uncoupled, and that local, not systemic, inflammation is a main determinant of changes in peritoneal small solute transport rate that is observed over time.…”
Section: Biomarker Research In the Context Of Chronic Peritoneal Inflmentioning
confidence: 97%
“…In pathological situations, angiogenesis is driven by an immune reaction that includes the secretion of proinflammatory cytokines particularly IL-1β, TNF-α [104] and IL-6 [105]. Secretion of IL-1β, TNF-α and IL-6 is hallmark of the early inflammatory phase of AE observed in mice [84].…”
Section: Discussionmentioning
confidence: 99%